2009
DOI: 10.1002/adma.200900525
|View full text |Cite
|
Sign up to set email alerts
|

TiO2‐Coated Multilayered SnO2 Hollow Microspheres for Dye‐Sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSSCs) have attracted extensive interest in past decade as a promising candidate for the future generation of cost-effective photovoltaic solar cells. [1][2][3][4][5] Since the first demonstration of 10.4% photoconversion efficiency on TiO 2 -based DSSC, [6] intensive work in DSSC research has been devoted to the synthetic chemistry and structural and photovoltaic characterization of mesoporous nanocrystalline TiO 2 materials. [7][8][9] In contrast, other metal oxide semiconductors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
406
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 551 publications
(417 citation statements)
references
References 30 publications
11
406
0
Order By: Relevance
“…Recent works have also revealed that multi-shelled hollow spheres exhibit a greatly enhanced photocatalytic activity or photoelectric conversion efficiency due to multiple-reflections of light [37,38]. To verify the multiple reflections effect in the multi-shelled hollow TiO2, double shelled TiO2 was synthesized by utilizing T450 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recent works have also revealed that multi-shelled hollow spheres exhibit a greatly enhanced photocatalytic activity or photoelectric conversion efficiency due to multiple-reflections of light [37,38]. To verify the multiple reflections effect in the multi-shelled hollow TiO2, double shelled TiO2 was synthesized by utilizing T450 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Over the past decades, semiconducting photocatalytic materials like ZnO, TiO 2 are widely applied for degradation and complete mineralization of toxic organic compounds in water, soil, and air (Zeng et al 2008;Qian et al 2009). Titania (TiO 2 ) based catalyst is widely applied for decomposition of toxic organic chemicals both in the aqueous and gas phase due to its unique properties like nontoxicity, chemical stability, high photocatalytic activity and low cost.…”
Section: Introductionmentioning
confidence: 99%
“…An optical scattering layer on top has been proposed as it could enhance the light harvest by localizing the incident light within the photoanode. So far, an array of light scattering materials has been investigated, including TiO2 mesoporous microspheres, 7,8 hollow spheres [9][10][11] and mirror-like nanoparticles. 12,13 Another major drawback of the conventional TiO2 nanoparticle photoanodes is the low transport efficiency of electrons, which imposes an upper limit on the film thickness.…”
Section: Introductionmentioning
confidence: 99%